I know following variants of SR flip flop:
So, by above approach, we are getting,
S = J'Q and R = KQ
However I did not find any text / website explaining how to convert AND-NOR SR flip flop to JK flip flop. So I tried myself as follows:
By above approach, we are getting
S=J'+KQ' and R=K'+Q'
I searched online for correctness of this. Didnt found anything. Only found this page which shows JK flip flip using NOR-NOR gates as follows:
This flip flop comes with KQ and JQ' which definitely does not match with what I have got.
Can someone tell, if I was correct with S=J'+KQ' and R=K'+Q' or I was wrong and the above diagram is correct?
After some more thinking, I feel I got it. As we have two implementations of SR flip flop, we are supposed to have two implementations of JK flip flop: 1st implementation replacing forbidden state in NAND-NAND SR flip flop with toggle state and 2nd implementation replacing forbidden state in AND-NOR SR flip flop with toggle state. What I was trying to do is using AND-NOR SR flip flop to prepare 1st implementation of JK flip flop!!! If I try to prepare 2nd implementation of JK flip flop with AND-NOR SR flip flop, I get something as follows:
The outcome looks more reasonable. I am getting S=J+Q and R=Q'+K unlike S=J'+KQ' and R=K'+Q' I earlier obtained. Do you feel this correct? I believe last image before edit is anyway incorrect, right?